2004
DOI: 10.1536/jhj.45.81
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Vein Dimensions and Variation of Branching Pattern in Patients With Paroxysmal Atrial Fibrillation Using Magnetic Resonance Angiography

Abstract: SUMMARYPulmonary veins are the most frequent origin of focal and paroxysmal atrial fibrillation. Although radiofrequency ablation has been attempted for the treatment of focal and paroxysmal atrial fibrillation, the anatomy of the pulmonary vein is still not fully understood. To investigate the dimensions and anatomical variation of the pulmonary vein in patients with paroxysmal atrial fibrillation, we performed breath-hold gadolinium enhanced magnetic resonance (MR) angiography using a 1.5 T cardiac MR imager… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 16 publications
2
13
0
Order By: Relevance
“…Recently, it has been shown that ectopic electrical activity in the sleeves of atrial myocardium extending 1-2 cm into the pulmonary veins (PVs) plays a central role in generating AF [4][5][6]. Th us, since the discovery that ectopic foci can originate in PVs and can be responsible for AF, pulmonary veins themselves became the targets of catheter directed radiofrequency ablation [7,8]. Electrical mapping for radiofrequency ablation in the pulmonary vein requires a clarifi cation of pulmonary vein anatomy, especially the pulmonary vein diameter and branching pattern and the characteristics of the left atrium to the pulmonary vein junction [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been shown that ectopic electrical activity in the sleeves of atrial myocardium extending 1-2 cm into the pulmonary veins (PVs) plays a central role in generating AF [4][5][6]. Th us, since the discovery that ectopic foci can originate in PVs and can be responsible for AF, pulmonary veins themselves became the targets of catheter directed radiofrequency ablation [7,8]. Electrical mapping for radiofrequency ablation in the pulmonary vein requires a clarifi cation of pulmonary vein anatomy, especially the pulmonary vein diameter and branching pattern and the characteristics of the left atrium to the pulmonary vein junction [7].…”
Section: Discussionmentioning
confidence: 99%
“…Th us, since the discovery that ectopic foci can originate in PVs and can be responsible for AF, pulmonary veins themselves became the targets of catheter directed radiofrequency ablation [7,8]. Electrical mapping for radiofrequency ablation in the pulmonary vein requires a clarifi cation of pulmonary vein anatomy, especially the pulmonary vein diameter and branching pattern and the characteristics of the left atrium to the pulmonary vein junction [7]. A variety of cardiac imaging modalities including conventional fl uoroscopy/ angiography, transesophageal or transthoracic echocardiography, intra-cardiac echocardiogram [9], multi-detector computed tomography (MDCT) and magnetic resonance imaging (MRI) have been used for catheter navigation during ablation procedures [10].…”
Section: Discussionmentioning
confidence: 99%
“…6C). Four PV diameters are reported to be greater in the order of patients with permanent AF > those with paroxysmal AF > those with sinus rhythm (Takase et al, 2004). Moreover, PV branching pattern observed in AF patients is complicated compared with that of patients with sinus rhythm.…”
Section: Pvf During Sinus Rhythm In Af Patientsmentioning
confidence: 97%
“…PV orifice morphologies in conjunction with AF progression have been investigated over the years by various modalities such as TEE (Knackstedt et al, 2003), magnetic resonance (MR) imaging (Tsao et al, 2001;Takase et al, 2004) and multislice computed tomography (Scharf et al, 2003). These investigations have been conducted under the uniform hypothesis that largest PV is the main source of ectopic electrical activities triggering and sustaining AF.…”
Section: Pvf During Sinus Rhythm In Af Patientsmentioning
confidence: 99%
“…No subject had either mitral regurgitation or aortic stenosis. MR imaging: MR [30][31][32][33] examination was performed using a Magnetom Vision (Siemens, Erlangen, Germany) instrument with a 1.5 Tesla superconducting magnet. A cine loop of LV short-axis images was obtained using an ECG trigger gradient refocused sequence (turbo-fast low angle shots).…”
Section: Diagnosis Of Hcm and Population For Analysismentioning
confidence: 99%